1992
DOI: 10.1901/jaba.1992.25-713
|View full text |Cite
|
Sign up to set email alerts
|

Brief Functional Assessment Techniques to Evaluate Aberrant Behavior in an Outpatient Setting: A Summary of 79 Cases

Abstract: Previous investigators have analyzed the maintaining conditions for aberrant behaviors using brief functional assessment procedures. These assessment procedures have been used in one of our outpatient clinics, the Self-Injurious and Aggressive Behavior Service. This study presents a descriptive summary of the results from 79 cases during a 3-year period. The outcomes of the brief assessment were evaluated across three variables: (a) referring topography, (b) control over behavior as evaluated through brief mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
197
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(211 citation statements)
references
References 10 publications
13
197
1
Order By: Relevance
“…Iwata, Pace, Dorsey, et al (1994) found that 23% of a series of 152 cases of self-injurious behavior were maintained by attention. Similarly, in a series of 79 cases of self-injurious or aggressive behavior, attention was hypothesized as the maintaining condition in 24% (Derby et al, 1992). It has been suggested (e.g., Durand & Crimmins, 1988b;McGill, 1993) that problem behavior maintained by attention is more likely to occur in environments characterized by low levels of social contact.…”
Section: Social-positive Reinforcementmentioning
confidence: 99%
See 2 more Smart Citations
“…Iwata, Pace, Dorsey, et al (1994) found that 23% of a series of 152 cases of self-injurious behavior were maintained by attention. Similarly, in a series of 79 cases of self-injurious or aggressive behavior, attention was hypothesized as the maintaining condition in 24% (Derby et al, 1992). It has been suggested (e.g., Durand & Crimmins, 1988b;McGill, 1993) that problem behavior maintained by attention is more likely to occur in environments characterized by low levels of social contact.…”
Section: Social-positive Reinforcementmentioning
confidence: 99%
“…Epidemiological studies suggest escape to be the most common reinforcer for problem behavior, representing 35% of cases of self-injurious behavior (Iwata, Pace, Dorsey, et al, 1994) and 48% of cases of self-injurious or aggressive behavior (Derby et al, 1992). Many authors (e.g., Smith & Iwata, 1997) have now pointed out that demands probably function as EOs (rather than S D s) evoking escape-maintained problem behavior.…”
Section: Social-negative Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducting experimental manipulations, similar to the Iwata et al (1982 study, and studies with at least two comparison conditions, as described by Derby et al (1992), were recorded under the category of reinforcement-or punishment-based procedures with a functional analysis. Studies using assessment procedures such as interviews, informal observations, rating scales, or scatter plots, as well as studies that did not conduct an experimental manipulation during assessment, were recorded under the category of reinforcement-or punishment-based procedures without a functional analysis.…”
Section: Inclusion Criteria For Articlesmentioning
confidence: 99%
“…One such condition is when the individual emits a low rate of problem behavior either in the naturalistic context or in the functional analysis. For example, Derby et al (1992) examined the results of 79 functional analyses. They failed to identify a behavioral function in 29 of those cases because the target behavior rarely occurred.…”
mentioning
confidence: 99%